The Dynamics of Youth Radicalization: The Mediating Role of Exposure to Political Violence in Shaping Sympathy for Radicalism - Bafadhal, Oemar Madri; Rahmawati, Annisa; Santoso, Anang Dwi (Jurnal Media dan Komunikasi Indonesia, 2026)
This study examines the relationship between radical content consumption, intensity of social media use, exposure to political violence, and sympathy for radicalism among youth. It contributes empirical evidence from Indonesian secondary-school students. Drawing on Terror Management Theory and media socialization research, the study argues that online exposure is not uniformly radicalizing, but depends on the kind of content encountered and its reinforcement through experiences of collective violence. Data were collected from 120 high school and vocational school students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that radical content consumption significantly increases exposure to political violence, which in turn increases sympathy for radicalism. By contrast, social media use intensity has no significant direct or indirect effect. However, radical content consumption affects sympathy for radicalism only indirectly through exposure to political violence. These findings suggest that youth radicalization is better understood as a mediated process shaped by content exposure and threat perception rather than by social media use alone. The article concludes with implications for prevention strategies centered on content exposure, digital literacy, and youth resilience.